A composite coating based on carbon dots, spiropyrans and super-slippery surface, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611234627.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]为了克服上述现有技术的缺点,本发明的目的在于提供一种基于碳点、螺吡喃和超滑表面的复合涂层及其制备方法和应用,用以解决现有荧光防伪材料动态防伪阶数低、环境耐受性差、以及因物理共混或物理吸附导致组分相容性差、易团聚脱落、发光不均匀、长期使用易荧光猝灭及防伪失效的技术问题
本发明提供了一种基于碳点、螺吡喃和超滑表面的复合涂层,该复合涂层包含时序型荧光防伪涂层以及超滑表面层,时序型荧光防伪涂层中通过酰胺键实现绿色碳点与羧基功能化螺吡喃的共价键合,有效提升了复合涂层的整体均匀性与结构稳定性,妥善解决了传统荧光防伪材料结构稳定性差、发光功能易失效、防伪信息易泄露等行业技术痛点;
Smart Images

Figure CN122878795A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dynamic light-emitting materials technology, specifically relating to a composite coating based on carbon dots, spiropyran and super-lubricating surfaces, its preparation method and application. Background Technology
[0002] With the proliferation of counterfeit and substandard products in the market, serious threats are posed to product safety, document authenticity, and food and drug traceability systems. Developing new anti-counterfeiting technologies and functional materials that are highly secure, difficult to imitate, and exhibit excellent stability is of significant practical importance and application value. Among numerous fluorescent functional materials, carbon dots have become a research hotspot in the fields of anti-counterfeiting packaging and information anti-counterfeiting due to their unique advantages, including excellent photoluminescence properties, wide availability of raw materials, low preparation costs, and good biocompatibility. However, traditional carbon dot anti-counterfeiting materials still have significant technical shortcomings. Most carbon dots possess only a single fluorescent emission characteristic, resulting in limited anti-counterfeiting information dimensions and coding capacity. They are easily imitated by mixing similar fluorescent materials, leading to low anti-counterfeiting security and insufficient identification, failing to meet the needs of high-end anti-counterfeiting applications.
[0003] To address the aforementioned issues, combining fluorescent materials with photochromic functional molecules and constructing dynamically tunable fluorescent systems based on the fluorescence resonance energy transfer (FRET) effect has become a mainstream research direction for high-performance dynamic luminescent anti-counterfeiting materials. Among them, spiropyrans are a typical photoresponsive smart color-changing molecule that can achieve reversible isomerization transitions between closed-ring (SP) and open-ring (MC) states under ultraviolet light stimulation, accompanied by significant changes in fluorescence and absorption spectra. It possesses advantages such as fast response speed, reversibility, low cost, and controllable structure, showing excellent application potential in fields such as information encryption and dynamic anti-counterfeiting.
[0004] Existing technologies have reported on the physical encapsulation or adsorption coexistence of carbon quantum dots and spiropyran through metal-organic frameworks (such as ZIF-8) (Chinese authorized patent publication number CN116554868B). This type of scheme utilizes the FRET effect to achieve a two-stage dynamic color change from blue to red fluorescence, which improves the dynamic nature of anti-counterfeiting information to a certain extent. However, this scheme has the following inherent defects: First, there is a lack of chemical bonding between carbon dots and spiropyran, and they are only physically blended or physically adsorbed, resulting in poor compatibility between components. During long-term use, aggregation, phase separation, and even functional component detachment are likely to occur, causing unstable and uncontrollable fluorescence response, and a significant decrease in anti-counterfeiting reliability over time. Second, this scheme can only achieve a two-stage (from blue to red) fluorescence color change, with a low dynamic anti-counterfeiting level and limited coding capacity, still facing the risk of being counterfeited, and is difficult to meet the needs of high-level dynamic anti-counterfeiting. Third, the product of this scheme is in powder form and does not involve coating applications, lacking consideration for adaptability to actual use environments.
[0005] In addition, existing fluorescent anti-counterfeiting coatings generally suffer from poor environmental tolerance. They do not possess excellent resistance to acids and alkalis, temperature and humidity, or aging. Under complex external environmental stimuli, they are prone to problems such as coating corrosion, peeling, and fluorescence quenching, which seriously damage the integrity of the anti-counterfeiting structure and significantly shorten the service life of the anti-counterfeiting materials. Summary of the Invention
[0006] In order to overcome the shortcomings of the prior art, the present invention aims to provide a composite coating based on carbon dots, spiropyran and super-lubricated surfaces, its preparation method and application, to solve the technical problems of existing fluorescent anti-counterfeiting materials, such as low dynamic anti-counterfeiting order, poor environmental tolerance, poor component compatibility due to physical blending or physical adsorption, easy agglomeration and shedding, uneven luminescence, easy fluorescence quenching and anti-counterfeiting failure after long-term use.
[0007] To achieve the above objectives, the present invention employs the following technical solution: This invention provides a composite coating based on carbon dots, spiropyran, and a super-slippery surface, comprising a substrate, wherein a time-series fluorescent anti-counterfeiting coating is disposed on the surface of the substrate, and a super-slippery surface layer is disposed on the surface of the time-series fluorescent anti-counterfeiting coating; the time-series fluorescent anti-counterfeiting coating contains a composite fluorescent product, wherein the composite fluorescent product comprises green carbon dots and carboxyl-functionalized spiropyran, the green carbon dots and carboxyl-functionalized spiropyran being covalently linked by amide bonds; the composite coating exhibits continuous dynamic time-series luminescence changes of green fluorescence, yellow fluorescence, and red fluorescence under ultraviolet light excitation.
[0008] Preferably, the super-slippery surface layer comprises a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer, wherein the Janus microcapsule pore structure of the amphiphilic hollow mesoporous silica Janus microcapsule layer is filled with silicone oil.
[0009] Preferably, the initial water contact angle hysteresis of the composite coating is less than 2°.
[0010] The present invention also provides a method for preparing the composite coating based on carbon dots, spiropyran, and super-lubricating surface, comprising the following steps: 1) Mix ionic liquid, carbon source and nitrogen source, heat to 80-150℃ and react at a constant temperature for 2-4 hours, then perform a first dialysis and freeze-drying to obtain green carbon dots; the mass ratio of ionic liquid to carbon source is 3:1, and the mass ratio of nitrogen source to carbon source is (1-3):1. 2) 2,3,3-trimethylindole and 3-bromopropionic acid are dissolved in a first organic solvent and subjected to a first reflux reaction to obtain an intermediate product; the intermediate product is then dissolved in a second organic solvent and subjected to a second reflux reaction to obtain a carboxyl-functionalized spiropyran; the mass ratio of 3-bromopropionic acid to 2,3,3-trimethylindole is (0.8-1.2):1; the mass ratio of 5-nitrosalicylic acid to the intermediate product is (0.6-1.0):1; 3) Mix the green carbon dot aqueous solution with the carboxyl-functionalized spiropyran solution, add a coupling agent, react at room temperature for 6-12 h, and then perform a second dialysis and freeze-drying to obtain a composite fluorescent product covalently linked by amide bonds; 4) The composite fluorescent product powder is added to the organic solution of hydroxyl acrylic resin to prepare a composite spraying liquid, which is then sprayed onto the substrate surface, dried and cured to obtain a time-series fluorescent anti-counterfeiting coating. 5) An ultra-slippery surface layer is prepared on the surface of the time-series fluorescent anti-counterfeiting coating to obtain the composite coating.
[0011] Preferably, the ionic liquid in step 1) is 1-butyl-3-methylimidazolium chloride, the carbon source is citric acid, and the nitrogen source is o-phenylenediamine; the conditions for the first dialysis treatment include: a molecular weight cutoff of 800-1000 Da and a time of 12-48 h.
[0012] Preferably, in step 2), the first organic solvent is toluene, the temperature of the first reflux reaction is 120-140 °C, and the time is 10-14 h. After the first reflux reaction is completed, the product is washed and dried with toluene to obtain the reaction intermediate. The second organic solvent is an ethanol solution, the temperature of the second reflux reaction is 60-80 °C, and the time is 6-8 h. After the second reflux reaction is completed, the product is dried to obtain the carboxyl-functionalized spiropyran product.
[0013] Preferably, in step 3), the concentration of the green carbon dot aqueous solution is 1 mg / mL, and the volume ratio of the carboxyl-functionalized spiropyran solution to the green carbon dot aqueous solution is (1-5):1; the coupling agent is a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, the mass ratio of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to the green carbon dot is (1-5):1, and the mass ratio of the N-hydroxysuccinimide to the green carbon dot is (1-3):1; the conditions for the second dialysis treatment include: a molecular weight cutoff of 1000-1300 Da and a time of 12-48 h.
[0014] Preferably, in step 4), the organic solution of the hydroxy acrylic resin is an acetone solution of the hydroxy acrylic resin; the concentration of the composite spraying liquid is 10 mg / mL - 50 mg / mL.
[0015] Preferably, in step 5), the step of preparing the super-slippery surface layer includes: sequentially spraying an acetone solution of polyurethane prepolymer and an acetone dispersion of amphiphilic hollow mesoporous silica Janus microcapsules onto the surface of the time-series fluorescent anti-counterfeiting coating to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer; drying in steps; and injecting silicone oil into the Janus microcapsule pore structure of the acetone dispersion of amphiphilic hollow mesoporous silica Janus microcapsules to obtain the composite coating; The acetone solution concentration of the polyurethane prepolymer was 0.10 g / mL - 0.40 g / mL, the acetone dispersion concentration of the amphiphilic hollow mesoporous silica Janus microcapsules was 1.0 g / mL - 2.0 g / mL, and the concentration of the silicone oil was 0.50 g / mL - 2.50 g / mL.
[0016] The present invention also provides the application of the composite coating in high-end document recognition, anti-counterfeiting of food and drug packaging, and anti-counterfeiting of precision device marking.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a composite coating based on carbon dots, spiropyran, and a super-slippery surface. The composite coating includes a time-sequential fluorescent anti-counterfeiting coating and a super-slippery surface layer. In the time-sequential fluorescent anti-counterfeiting coating, green carbon dots and carboxyl-functionalized spiropyran are covalently bonded through amide bonds, which effectively improves the overall uniformity and structural stability of the composite coating. This invention properly solves the technical pain points of traditional fluorescent anti-counterfeiting materials, such as poor structural stability, easy failure of luminescent function, and easy leakage of anti-counterfeiting information. The formation of amide bonds ensures that the two components are not simply physically mixed, but rather form a fixed donor-acceptor pair. Under UV excitation, the green light emitted by G-CDs acts as an internal filtering effect / energy transfer source for carboxyl-functionalized spiropyran. The carboxyl-functionalized spiropyran undergoes reversible spirocyclic-metacyanine isomerization under illumination, accompanied by a redshift of the absorption / emission peaks, thus exhibiting continuous dynamic time-series luminescence from green fluorescence to yellow fluorescence to red fluorescence. This completely breaks through the static and singular anti-counterfeiting limitations of traditional anti-counterfeiting materials, constructing a dynamic and variable new anti-counterfeiting system and significantly increasing the difficulty of cracking anti-counterfeiting measures. Covalent bonding ensures a constant spatial distance and repeatable energy / electron interactions between the two components, forming the structural basis for the stability of the time-series signal. This invention innovatively introduces an ultra-slippery surface layer, which forms an extremely low surface energy and extremely low adhesion barrier on the outside of the time-series fluorescent anti-counterfeiting coating. Externally, it isolates the fluorescent molecules from the attack of water, oxygen, acids, alkalis, and mechanical friction; internally, it reduces fluorescence self-quenching. This not only endows the composite coating with excellent anti-fouling properties, preventing stains from interfering with anti-counterfeiting identification, but also effectively blocks interfering media such as oxygen and water vapor in the environment that inhibit carbon point luminescence, significantly improving the fluorescence intensity and luminescence stability of the composite material. This structure effectively improves the poor environmental tolerance of traditional fluorescent anti-counterfeiting materials, greatly enhances the coating's anti-interference and anti-aging capabilities, and effectively extends the service life of the anti-counterfeiting coating.
[0018] The composite coating of this invention exhibits a continuous dynamic time-series luminescence change from green fluorescence to yellow fluorescence to red fluorescence under ultraviolet light excitation, possessing both unique dynamic anti-counterfeiting characteristics and excellent super-slippery properties with an initial water contact angle hysteresis of less than 2°. To verify environmental resistance, the composite coating of this invention and the pure anti-counterfeiting coating without a super-slippery surface layer were immersed in solutions of pH=1, pH=7, and pH=13 for 3 days, respectively. The results showed that the fluorescence intensity decay rate of this invention was only 27.74%, 26.74%, and 35.71%, far lower than that of the control group (52.83%, 51.10%, and 56.84%). Furthermore, after acid and alkali immersion, its water contact angle hysteresis remained stably maintained at a low level of less than 6°, demonstrating excellent resistance to acid and alkali corrosion and anti-fouling durability. Furthermore, thanks to the effective physical barrier of the super-smooth surface layer against fluorescence quenching media such as water molecules and oxygen, the fluorescence intensity of this coating at 530 nm during initial ultraviolet light irradiation is 10.27% higher than that of the pure anti-counterfeiting coating, and the fluorescence intensity at 650 nm after 60 s of irradiation is 35.18% higher, achieving a synergistic enhancement of anti-counterfeiting luminescent signal intensity and long-term stability.
[0019] Furthermore, the super-slippery surface layer is defined by three functional units, which achieve the following beneficial effects: Polyurethane prepolymer layer: As the bonding base layer, it ensures a firm bond between the ultra-slippery surface layer and the underlying time-sequential fluorescent anti-counterfeiting coating, preventing the protection from failing due to delamination; Amphiphilic hollow mesoporous silica Janus microcapsule layer: Janus microcapsules are amphiphilic with one side being hydrophilic and the other side being hydrophobic, and their hollow mesoporous structure can store lubricating oil; their arrangement on the coating surface forms a micro oil reservoir. Silicone oil filling the pores: Silicone oil acts as a lubricant / hydrophobic agent, giving the surface extremely low surface energy and self-healing properties. When Janus microcapsules are damaged, silicone oil can seep out to replenish itself. This structure integrates adhesion, oil storage, and lubrication, making the super-slippery surface layer not only initially smooth but also possessing a certain self-healing ability, thus maintaining a low-adhesion, low-pollution state for a long time and protecting the inner fluorescent molecules.
[0020] Furthermore, the initial water contact angle hysteresis is <2°, resulting in extremely low and uniform surface energy of the composite coating, with droplets almost in a ball-and-ball state on the surface; the liquid does not easily remain, avoiding interference from the water film on the anti-reflection / scattering of the time-series fluorescent anti-counterfeiting coating and its catalysis of spiropyran hydrolysis; the extremely low hysteresis also means extremely low surface adhesion, making it difficult for external pollutants to adhere, indirectly protecting the dynamic fluorescent signal from being obscured.
[0021] Furthermore, the initial irradiation at 530 nm improved by 10.27%: the super-smooth surface layer reduced Fresnel reflection loss and scattering at the air-time-sequential fluorescent anti-counterfeiting coating interface, allowing more excitation light to enter the time-sequential fluorescent anti-counterfeiting coating and more emission light to emerge; at the same time, the inert atmosphere of the silicone oil reduced the surface oxygen quenching of G-CDs; After 60 s of irradiation, the red light signal at 650 nm increased by 35.18%: As UV irradiation continued, spiropyran gradually isomerized into anthocyanin, and the red light signal at 650 nm was enhanced; the super-lubricated surface layer continuously isolated oxygen during this stage, inhibiting the oxidative degradation and anti-isomerization of anthocyanin, resulting in a greater increase in red light signal compared to the control without super-lubricated surface layer (35.18% > 10.27%).
[0022] The super-smooth surface layer has a particularly significant protective effect on the red light signal in the later stage of the dynamic process, directly enhancing the recognizability of the red stage in the time-series luminescence and improving the contrast of dynamic anti-counterfeiting.
[0023] Furthermore, after immersion in acid and alkali for 3 days, the fluorescence decay rates were 27.74%, 26.74%, and 35.71%. Under extreme pH conditions, fluorescent molecules inevitably experience some decay, but the super-slippery surface layer plays a crucial buffering and barrier role, allowing the silicone oil and Janus microcapsules to form a hydrophobic barrier, slowing down the H+ degradation. + / OH - The diffusion rate to the time-series fluorescent anti-counterfeiting coating; the polyurethane prepolymer layer prevents the overall peeling off of the composite coating; The water contact angle hysteresis remained <6° after immersion, demonstrating that even under extreme erosion at pH=1 or pH=13, the super-slippery surface layer structure remained intact and maintained its low adhesion properties. This means that the anti-counterfeiting label can continue to function effectively in harsh environments such as outdoor settings, cold chain environments, high humidity, and acid / alkali contact. Therefore, the super-smooth surface layer reduces the intrusion rate of external corrosive media, thereby improving the lifetime of dynamic fluorescence signals from short-term display to long-term reliability.
[0024] This invention also provides a method for preparing the composite coating based on carbon dots, spiropyran, and a super-lubricating surface: Step 1) The ionic liquid functions as both a solvent and a nitrogen dopant. The nitrogen source is pyrolyzed at high temperature to form green carbon dots, whose emission wavelength matches the absorption window of spiropyran, laying the foundation for subsequent energy transfer / internal filtration effects. Step 2) A carboxyl group is introduced by reacting 2,3,3-trimethylindole with 3-bromopropionic acid, followed by condensation with 5-nitrosalicylaldehyde to obtain COOH-SP; the carboxyl group is the reaction site for subsequent formation of an amide bond with the amino group of G-CDs; Step 3) After the EDC / NHS activates the carboxyl groups, it dehydrates with the amino groups on the surface of G-CDs to form amide bonds, resulting in a covalently linked G-CDs@COOH-SP composite fluorescent product. This covalent linkage (as opposed to physical mixing) ensures a fixed donor-acceptor distance, stable energy transfer efficiency, and reproducible excitation, which is beneficial for stable and reproducible time-series signals. Step 4) Hydroxy acrylic resin provides mechanical support and film-forming properties, enabling the time-series fluorescent anti-counterfeiting coating to adhere firmly to the substrate; Step 5) The time-series fluorescent anti-counterfeiting coating and the super-slippery surface layer together form a dual-layer protection system.
[0025] Furthermore, by limiting the ionic liquid to 1-butyl-3-methylimidazolium chloride, the carbon source to citric acid, and the nitrogen source to o-phenylenediamine, this combination, after process optimization, can obtain green carbon dots with emission peaks at ~530 nm, which have the best overlap with the absorption spectrum of spiropyran and the highest energy transfer efficiency. With a molecular weight cutoff of 800-1000 Da, this range effectively removes unreacted small molecule precursors, byproducts, and low molecular weight impurities while retaining the target carbon dots (typically with molecular weights in the thousands to tens of thousands). Purification reduces surface defects in the carbon dots, suppresses non-radiative transition pathways, and improves fluorescence stability. A dialysis time of 12-48 h ensures sufficient time for impurities to diffuse completely, preventing residual acidic or basic substances from interfering with the reaction or causing carbon dot aggregation in subsequent amide coupling steps.
[0026] Therefore, the first dialysis treatment conditions yielded G-CDs with higher purity and more regular surface functional groups, providing reliable active sites for their covalent connection with COOH-SP, thereby ensuring the repeatability and long-term stability of dynamic time-series signals.
[0027] Furthermore, in the first reflux reaction, the first organic solvent, toluene, has a high boiling point (110.6℃), which can support a reflux temperature of 120-140℃, promoting the SN2 substitution reaction of 2,3,3-trimethylindole with 3-bromopropionic acid and increasing the yield; temperature 120-140℃ and time 10-14 h: these conditions ensure the reaction proceeds fully, avoiding incomplete conversion of intermediates due to excessively low temperature or insufficient time, which would affect the carboxyl content of subsequent spiropyran; toluene washing: toluene can dissolve unreacted raw materials and byproducts, while the product is insoluble in toluene, achieving efficient purification.
[0028] Therefore, the first heating and reflux reaction is beneficial for obtaining reaction intermediates with high purity and high carboxyl content, providing sufficient active sites for the second condensation step.
[0029] In the second reflux reaction, the second organic solvent, ethanol solution, has moderate polarity, which can dissolve the reaction intermediates and 5-nitrosalicylic acid without excessively accelerating the side reactions; the mild conditions of 60-80℃ and 6-8 h prevent the spiropyran ring from opening and decomposing at high temperatures, while ensuring complete condensation; the drying process removes residual ethanol and water, preventing water molecules from competing to activate the ester during subsequent amide coupling.
[0030] The second heating and reflux reaction yields a carboxyl-functionalized spiropyran with a complete structure, high carboxyl group density, and few impurities. The high carboxyl group density means that more sites can form amide bonds with the amino groups on G-CDs, thereby establishing a dense energy transfer network in the covalently linked product, making dynamic fluorescence changes more sensitive and providing higher contrast.
[0031] Furthermore, the concentration of the green carbon dot aqueous solution was 1 mg / mL, which maintained the high fluorescence quantum yield of the carbon dots at the molecular level, providing a stable luminescent substrate for subsequent covalent connection with spiropyran, and directly enhancing the initial signal intensity of the dynamic anti-counterfeiting signal. The volume ratio of carboxyl-functionalized spiropyran solution to green carbon dot aqueous solution is 1-5:1. By adjusting this ratio, the dynamic fluorescence contrast of green, yellow, and red can be optimized, making the color transition of the three stages more distinct and improving the reliability of anti-counterfeiting identification. At the same time, this ratio range avoids extreme cases of being too low (weak signal) or too high (self-quenching due to steric hindrance), balancing signal strength and structural stability. The mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dots is (1-5):1. EDC activates the carboxyl groups to form an intermediate, and its amount must be sufficient to cover all carboxyl groups on COOH-SP. If the ratio is too low, activation will be incomplete, and a large amount of spiropyran will not be able to connect to the carbon dots, remaining free in the system; if the ratio is too high, it may trigger side reactions or increase the purification burden. The mass ratio of N-hydroxysuccinimide to green carbon dots is (1-3):1. NHS converts the activated intermediate into a more stable NHS ester, improving the amide bond formation efficiency. This ratio ensures that NHS can fully stabilize the activated ester in the presence of EDC, extending the coupling window period. Therefore, the synergistic effect of the mass ratio of the two components optimizes the amide bond grafting rate between G-CDs and COOH-SP. A high grafting rate means a denser covalent network, more energy transfer pathways, and a more sensitive and stable dynamic fluorescence response. At the same time, the amount of unreacted free spiropyran is minimal, avoiding background interference caused by its migration, crystallization, or spontaneous ring-opening during subsequent film formation, thus significantly improving the long-term stability of the anti-counterfeiting signal. The molecular weight cutoff in the second dialysis treatment ensures that the second dialysis can effectively remove uncoupled free spiropyran (often with a molecular weight of several hundred), excess coupling agent and its byproducts, while retaining the target complex. After thorough purification, the complex product does not contain impurities that interfere with the sequential luminescence, so that the dynamic fluorescence signal does not show abnormal shifts or attenuation under long-term use or repeated excitation, directly contributing to long-term stability. Sufficient dialysis time can thoroughly remove residual EDC, NHS, and their hydrolysis products from the reaction system. If these impurities remain in the coating, they may produce non-specific fluorescence or accelerate the degradation of spiropyran under ultraviolet irradiation. This dialysis time ensures a high level of chemical purity in the composite product, thereby significantly enhancing the anti-interference capability and lifespan of the dynamic anti-counterfeiting signal in subsequent coating preparation and practical applications.
[0032] Furthermore, an acetone solution of polyurethane prepolymer is first sprayed and dried to form an adhesive underlayer. Then, an acetone dispersion of amphiphilic hollow mesoporous silica Janus microcapsules is sprayed and dried to fix the microcapsules on the underlayer. This step-by-step operation avoids interference between the two components, ensuring that the microcapsules are evenly distributed and firmly bonded to the underlayer. By limiting the concentrations of the composite spray liquid, the acetone solution of the polyurethane prepolymer, the acetone dispersion of the amphiphilic hollow mesoporous silica Janus microcapsules, and the silicone oil concentration, appropriate thicknesses for each layer were ensured: the time-sequential fluorescent anti-counterfeiting coating was thick enough to guarantee signal strength, while the ultra-slippery surface layer was thin enough to avoid blocking fluorescence, yet dense enough to isolate external elements. These parameters together achieved a balance between maximizing signal strength and optimizing protective effect.
[0033] This invention also provides the application of the composite coating in high-end document recognition or anti-counterfeiting of food and drug packaging, the beneficial effects of which are reflected in: The dynamic timing signal (from green to yellow, and then from yellow to red) is difficult to counterfeit using conventional methods such as printing, photocopying, and scanning, resulting in a high level of anti-counterfeiting. The ultra-smooth surface layer protects the anti-counterfeiting features from fading and becoming ineffective under long-term use of documents and under the friction, temperature, humidity, and weak acid and alkali environments of food packaging, transportation, and storage. The signal strength improvement (530 nm -10.27%, 650 nm -35.18%) allows identification devices to clearly distinguish the signal without the need for expensive instruments; The low contact angle hysteresis (<6°) after acid and alkali resistance ensures reliable operation even in environments where food and pharmaceuticals may come into contact with oils, acidic beverages, alkaline cleaning agents, etc.
[0034] In summary, the composite coating of this invention not only revolutionizes the traditional single static anti-counterfeiting technology system, but also overcomes the core technical defects of insufficient environmental stability and limited fluorescence intensity of fluorescent anti-counterfeiting materials. It dually improves anti-counterfeiting security, unique identification, and scene adaptability, and can be widely used in various high-end anti-counterfeiting scenarios such as high-end document anti-counterfeiting identification, high-end food and drug packaging, and precision device marking anti-counterfeiting. It has the advantages of wide application range, strong stability, and high practical value, and has broad market application prospects. Attached Figure Description
[0035] Figure 1 Fourier transform infrared spectra of G-CDs, COOH-SP and G-CDs@COOH-SP in Example 1 of the present invention; Figure 2 The fluorescence spectrum of G-CDs in Example 1 of this invention; Figure 3 The fluorescence spectrum of COOH-SP in Example 1 of this invention; Figure 4 The fluorescence color change of G-CDs@COOH-SP(1:2) prepared in Example 1 of this invention after irradiation with 365 nm ultraviolet light for different times, and the fluorescence emission spectrum (a) and CIE coordinate change (b) under excitation at 365 nm wavelength. Figure 5 The image shows the fatigue resistance test results of G-CDs@COOH-SP(1:2) prepared in Example 1 of this invention. Figure 6 Optical appearance images of G-CDs@COOH-SP coating and G-CDs@COOH-SP SLIPS prepared in Example 1 of this invention under natural light (a) and 365 nm ultraviolet light irradiation for 60 s (b); Figure 7The fluorescence intensity changes of G-CDs@COOH-SP coating and G-CDs@COOH-SP SLIPS prepared in Example 1 of this invention after soaking in solutions with pH=1, 7, and 13 for 3 days and irradiated with 365 nm ultraviolet light at 0 s (a) and 60 s (b) at 650 nm are shown. Figure 8 The changes in water contact angle and contact angle hysteresis of G-CDs@COOH-SP SLIPS prepared in Example 1 of this invention after soaking in solutions with pH=1, 7, and 13 for 3 days. Detailed Implementation
[0036] To enable those skilled in the art to understand the features and effects of the present invention, the following descriptions and definitions are only general descriptions of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in the event of any conflict, the definitions in this specification shall prevail.
[0037] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0038] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0039] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0040] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0041] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0042] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" represents weight percentage, "parts" represents parts by weight, and "ratio" represents weight proportion.
[0043] This invention provides a time-series fluorescent anti-counterfeiting and anti-fouling composite coating based on carbon dots, spiropyran, and super-lubricating surfaces, its preparation method, and its application, which have the following beneficial effects: 1) Traditional fluorescent composite materials often employ physical blending, which suffers from poor component compatibility, easy agglomeration, easy phase separation, uneven luminescence, easy fluorescence quenching after long-term use, and anti-counterfeiting failure. This invention achieves covalent bonding of G-CDs and COOH-SP through an EDC / NHS catalytic system, replacing the traditional physical doping method. This results in tighter molecular bonding and more uniform dispersion between the two phases, effectively preventing material agglomeration, component shedding, and functional leakage. It ensures a stable, controllable, and repeatable time-series fluorescence response, significantly improving the material's optical stability and lifespan.
[0044] 2) Existing fluorescent anti-counterfeiting coatings generally suffer from drawbacks such as poor resistance to acids and alkalis, poor resistance to temperature and humidity, susceptibility to contamination, easy aging, and poor mechanical wear resistance. They are prone to damage and fluorescence failure in complex environments, resulting in short service life and poor adaptability to various scenarios. This invention innovatively constructs an ultra-slippery surface layer. This ultra-slippery surface layer has excellent light transmittance, does not interfere with the dynamic fluorescent anti-counterfeiting effect of the underlying layer, and simultaneously imparts an ultra-low water contact angle hysteresis (less than 2°) to the composite coating, providing excellent self-cleaning and anti-fouling properties. Furthermore, the ultra-slippery surface layer effectively isolates external interferences such as acid and alkali corrosion, temperature and humidity fluctuations, and contaminant adhesion, significantly improving the coating's environmental tolerance.
[0045] 3) The composite coating of this invention exhibits a continuous dynamic sequential luminescence change of "green fluorescence—yellow fluorescence—red fluorescence" under ultraviolet light excitation, possessing both unique dynamic anti-counterfeiting characteristics and excellent super-slippery performance with an initial water contact angle hysteresis of less than 2°. Furthermore, this composite coating demonstrates outstanding wear resistance and stability, stably retaining its core functions of dynamic fluorescence anti-counterfeiting and super-slippery anti-fouling even under complex external environmental interference, with extremely low performance degradation. This effectively solves the problems of traditional anti-counterfeiting coatings being susceptible to acid and alkali damage, prone to failure, and unable to maintain anti-fouling performance for a long time, significantly extending the material's service life and operational stability.
[0046] The composite coating of this invention features a simple overall preparation method, mild reaction conditions, good repeatability, and strong controllability, enabling large-scale batch production. The resulting composite coating integrates multiple excellent properties, including dynamic high-level anti-counterfeiting, self-cleaning and anti-fouling, acid and alkali resistance, aging resistance, and high wear resistance. It can be precisely adapted to high-precision, high-stability, and high-security high-end anti-counterfeiting scenarios such as high-end document recognition and high-end anti-counterfeiting packaging for food and pharmaceuticals, showing broad prospects for industrial application.
[0047] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0048] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" represents weight percentage, "parts" represents parts by weight, and "ratio" represents weight proportion.
[0049] Example 1 (1) Preparation of covalently linked amide-bonded composite fluorescent products (G-CDs@COOH-SP) 1-Butyl-3-methylimidazolium chloride, citric acid, and o-phenylenediamine (100% by mass of citric acid) were placed in a three-necked flask. The mass of 1-butyl-3-methylimidazolium chloride was 300% by mass of citric acid. The mixture was heated to 80 °C and reacted at this temperature for 2 h. After the reaction was complete, the resulting product was placed in a dialysis bag with a molecular weight cutoff of 800-1000 Da and dialyzed for 48 h. Finally, the product was freeze-dried to obtain green carbon dots, G-CDs.
[0050] 2,3,3-Trimethylindole and 3-bromopropionic acid (80% by weight of 2,3,3-trimethylindole) were dissolved in toluene solution and refluxed at 120 °C for 10 h. After the reflux reaction, the product was washed with toluene and dried to obtain a reaction intermediate. Subsequently, the obtained intermediate was dissolved in ethanol solution with 5-nitrosalicylic acid (60% by weight of the intermediate) and refluxed at 80 °C for 6 h. After the reaction was completed, the product was dried to finally obtain the carboxyl-functionalized spiropyran product, COOH-SP.
[0051] A 1 mg / mL aqueous solution of G-CDs was added to a COOH-SP solution containing 200% (w / w) of the G-CDs aqueous solution. A coupling agent, a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, was then added to the mixture. The mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dots was 5:1, and the mass ratio of N-hydroxysuccinimide to green carbon dots was 1:1. The mixture was reacted at room temperature for 12 h. After the reaction, the resulting product was dialyzed for 48 h in a dialysis bag with a molecular weight cutoff of 1000-1300 Da to remove residual impurities and unreacted materials. Finally, the purified product was freeze-dried to obtain a covalently linked composite fluorescent product, G-CDs@COOH-SP, via amide bonds.
[0052] (2) Construction of time-series fluorescent anti-counterfeiting coating Acetone dispersion powder of G-CDs@COOH-SP with a concentration of 10 mg / mL was thoroughly mixed and stirred evenly with acetone solution of hydroxy acrylic resin to obtain a uniform and stable composite spray liquid. The above spray liquid was uniformly sprayed onto the substrate surface, and after drying and curing, a time-series fluorescent anti-counterfeiting coating, G-CDs@COOH-SPcoating, was formed on the substrate surface.
[0053] (3) Construction of composite coating On the surface of the prepared time-series fluorescent anti-counterfeiting coating, an acetone solution of 0.10 g / mL polyurethane prepolymer and an acetone dispersion of 1.0 g / mL amphiphilic hollow mesoporous silica Janus microcapsules were sequentially sprayed to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer. After stepwise drying, silicone oil with a concentration of 0.50 g / mL was injected into the microcapsule pore structure to finally construct a functional composite coating, G-CDs@COOH-SP SLIPS, which has both dynamic time-series fluorescent anti-counterfeiting and excellent anti-fouling properties.
[0054] Example 2 (1) Preparation of covalently linked amide-bonded composite fluorescent products (G-CDs@COOH-SP) A certain amount of 1-butyl-3-methylimidazolium chloride, citric acid, and o-phenylenediamine (150% of the mass of citric acid) were placed in a three-necked flask. The mass of 1-butyl-3-methylimidazolium chloride was 300% of the mass of citric acid. The mixture was heated to 100 °C and reacted at this temperature for 3 h. After the reaction was completed, the resulting product was placed in a dialysis bag with a molecular weight cutoff of 800-1000 Da and dialyzed for 12 h. Finally, the product was freeze-dried to obtain green carbon dots, G-CDs.
[0055] 2,3,3-Trimethylindole and 90% (by weight) of 3-bromopropionic acid (by mass) of 2,3,3-trimethylindole were dissolved in toluene solution and refluxed at 130 °C for 11 h. After the reflux reaction was completed, the product was washed with toluene and dried to obtain a reaction intermediate. Subsequently, the obtained intermediate was dissolved in ethanol solution with 60% (by mass) of 5-nitrosalicylic acid (by mass) of the intermediate and refluxed at 60 °C for 6 h. After the reaction was completed, the product was dried to finally obtain the carboxyl-functionalized spiropyran product, COOH-SP.
[0056] A 1 mg / mL aqueous solution of G-CDs was added to a COOH-SP solution containing 100% of the G-CDs aqueous solution. A coupling agent, a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, was then added to the mixture. The mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dots was 5:1, and the mass ratio of N-hydroxysuccinimide to green carbon dots was 1:1. The mixture was reacted at room temperature for 6 h. After the reaction, the resulting product was dialyzed for 12 h in a dialysis bag with a molecular weight cutoff of 1000-1300 Da to remove residual impurities and unreacted materials. Finally, the purified product was freeze-dried to obtain a covalently linked composite fluorescent product, G-CDs@COOH-SP, via amide bonds.
[0057] (2) Construction of time-series fluorescent anti-counterfeiting coating Acetone dispersion powder of G-CDs@COOH-SP with a concentration of 20 mg / mL was thoroughly mixed and stirred evenly with acetone solution of hydroxy acrylic resin to obtain a uniform and stable composite spray liquid. The above spray liquid was uniformly sprayed onto the substrate surface, and after drying and curing, a time-series fluorescent anti-counterfeiting coating, G-CDs@COOH-SPcoating, was formed on the substrate surface.
[0058] (3) Construction of composite coating On the surface of the prepared time-series fluorescent anti-counterfeiting coating, an acetone solution of 0.10 g / mL polyurethane prepolymer and an acetone dispersion of 1.5 g / mL amphiphilic hollow mesoporous silica Janus microcapsules were sequentially sprayed to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer. After stepwise drying, silicone oil with a concentration of 1.50 g / mL was injected into the microcapsule pore structure to finally construct a functional composite coating, G-CDs@COOH-SP SLIPS, which has both dynamic time-series fluorescent anti-counterfeiting and excellent anti-fouling properties.
[0059] Example 3 (1) Preparation of covalently linked amide-bonded composite fluorescent products (G-CDs@COOH-SP) A certain amount of 1-butyl-3-methylimidazolium chloride, citric acid, and o-phenylenediamine (180% of the mass of citric acid) were placed in a three-necked flask. The mass of 1-butyl-3-methylimidazolium chloride was 300% of the mass of citric acid. The mixture was heated to 120 °C and reacted at this temperature for 2 h. After the reaction was completed, the resulting product was placed in a dialysis bag with a molecular weight cutoff of 800-1000 Da and dialyzed for 20 h. Finally, the product was freeze-dried to obtain green carbon dots, G-CDs.
[0060] 2,3,3-Trimethylindole and 100% (by weight) 3-bromopropionic acid of 2,3,3-trimethylindole were dissolved in toluene solution and refluxed at 140 °C for 12 h. After the reflux reaction, the product was washed with toluene and dried to obtain a reaction intermediate. Subsequently, the obtained intermediate was dissolved in ethanol solution with 70% (by weight) 5-nitrosalicylic acid of the intermediate and refluxed at 70 °C for 7 h. After the reaction was completed, the product was dried to finally obtain the carboxyl-functionalized spiropyran product, COOH-SP.
[0061] A 1 mg / mL aqueous solution of G-CDs was added to a 300% COOH-SP solution containing the G-CDs aqueous solution. A coupling agent, a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, was then added to the mixture. The mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dots was 5:1, and the mass ratio of N-hydroxysuccinimide to green carbon dots was 1:1. The mixture was reacted at room temperature for 8 h. After the reaction, the resulting product was dialyzed for 20 h in a dialysis bag with a molecular weight cutoff of 1000-1300 Da to remove residual impurities and unreacted materials. Finally, the purified product was freeze-dried to obtain a covalently linked composite fluorescent product, G-CDs@COOH-SP, via amide bonds.
[0062] (2) Construction of time-series fluorescent anti-counterfeiting coating Acetone dispersion powder of G-CDs@COOH-SP with a concentration of 30 mg / mL was thoroughly mixed and stirred evenly with acetone solution of hydroxy acrylic resin to obtain a uniform and stable composite spray liquid. The above spray liquid was uniformly sprayed onto the substrate surface, and after drying and curing, a time-series fluorescent anti-counterfeiting coating, G-CDs@COOH-SPcoating, was formed on the substrate surface.
[0063] (3) Construction of composite coating On the surface of the prepared time-series fluorescent anti-counterfeiting coating, an acetone solution of 0.20 g / mL polyurethane prepolymer and an acetone dispersion of 1.00 g / mL amphiphilic hollow mesoporous silica Janus microcapsules were sequentially sprayed to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer. After stepwise drying, silicone oil with a concentration of 2.00 g / mL was injected into the microcapsule pore structure to finally construct a functional composite coating, G-CDs@COOH-SP SLIPS, which has both dynamic time-series fluorescent anti-counterfeiting and excellent anti-fouling properties.
[0064] Example 4 (1) Preparation of covalently linked amide-bonded composite fluorescent products (G-CDs@COOH-SP) A certain amount of 1-butyl-3-methylimidazolium chloride, citric acid, and o-phenylenediamine (190% of the mass of citric acid) were placed in a three-necked flask. The mass of 1-butyl-3-methylimidazolium chloride was 300% of the mass of citric acid. The mixture was heated to 110 °C and reacted at this temperature for 2.5 h. After the reaction, the resulting product was placed in a dialysis bag with a molecular weight cutoff of 800-1000 Da and dialyzed for 24 h. Finally, the product was freeze-dried to obtain green carbon dots, G-CDs.
[0065] 2,3,3-Trimethylindole and 3-bromopropionic acid (90% by weight of 2,3,3-trimethylindole) were dissolved in toluene solution and refluxed at 120 °C for 10 h. After the reflux reaction, the product was washed with toluene and dried to obtain a reaction intermediate. Subsequently, the obtained intermediate was dissolved in ethanol solution with 5-nitrosalicylic acid (80% by weight of the intermediate) and refluxed at 70 °C for 8 h. After the reaction was completed, the product was dried to finally obtain the carboxyl-functionalized spiropyran product, COOH-SP.
[0066] A 1 mg / mL aqueous solution of G-CDs was added to a COOH-SP solution containing 400% (w / w) of the G-CDs aqueous solution. A coupling agent, a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, was then added to the mixture. The mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dots was 5:1, and the mass ratio of N-hydroxysuccinimide to green carbon dots was 1:1. The mixture was reacted at room temperature for 10 h. After the reaction, the resulting product was dialyzed for 24 h in a dialysis bag with a molecular weight cutoff of 1000-1300 Da to remove residual impurities and unreacted materials. Finally, the purified product was freeze-dried to obtain a covalently linked composite fluorescent product, G-CDs@COOH-SP, via amide bonds.
[0067] (2) Construction of time-series fluorescent anti-counterfeiting coating Acetone dispersion powder of G-CDs@COOH-SP with a concentration of 40 mg / mL was thoroughly mixed and stirred evenly with acetone solution of hydroxy acrylic resin to obtain a uniform and stable composite spray liquid. The above spray liquid was uniformly sprayed onto the substrate surface, and after drying and curing, a time-series fluorescent anti-counterfeiting coating, G-CDs@COOH-SPcoating, was formed on the substrate surface.
[0068] (3) Construction of composite coating On the surface of the prepared time-series fluorescent anti-counterfeiting coating, an acetone solution of 0.25 g / mL polyurethane prepolymer and an acetone dispersion of 1.50 g / mL amphiphilic hollow mesoporous silica Janus microcapsules were sequentially sprayed to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer. After stepwise drying, silicone oil with a concentration of 2.00 g / mL was injected into the microcapsule pore structure to finally construct a functional composite coating, G-CDs@COOH-SP SLIPS, which has both dynamic time-series fluorescent anti-counterfeiting and excellent anti-fouling properties.
[0069] Example 5 (1) Preparation of covalently linked amide-bonded composite fluorescent products (G-CDs@COOH-SP) A certain amount of 1-butyl-3-methylimidazolium chloride, citric acid, and o-phenylenediamine (200% of the mass of citric acid) were placed in a three-necked flask. The mass of 1-butyl-3-methylimidazolium chloride was 300% of the mass of citric acid. The mixture was heated to 130 °C and reacted at this temperature for 2.5 h. After the reaction was completed, the resulting product was placed in a dialysis bag with a molecular weight cutoff of 800-1000 Da and dialyzed for 36 h. Finally, the product was freeze-dried to obtain green carbon dots, G-CDs.
[0070] 2,3,3-Trimethylindole and 100% (by weight) 3-bromopropionic acid of 2,3,3-trimethylindole were dissolved in toluene solution and refluxed at 120 °C for 12 h. After the reflux reaction, the product was washed with toluene and dried to obtain a reaction intermediate. Subsequently, the obtained intermediate was dissolved in ethanol solution with 90% (by weight) 5-nitrosalicylic acid of the intermediate and refluxed at 80 °C for 7 h. After the reaction was completed, the product was dried to finally obtain the carboxyl-functionalized spiropyran product, COOH-SP.
[0071] A 1 mg / mL aqueous solution of G-CDs was added to a 500% COOH-SP solution containing the G-CDs aqueous solution. A coupling agent, a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, was then added to the mixture. The mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dots was 3:1, and the mass ratio of N-hydroxysuccinimide to green carbon dots was 2:1. The mixture was reacted at room temperature for 8 h. After the reaction, the resulting product was dialyzed for 48 h in a dialysis bag with a molecular weight cutoff of 1000-1300 Da to remove residual impurities and unreacted materials. Finally, the purified product was freeze-dried to obtain a covalently linked composite fluorescent product, G-CDs@COOH-SP, via amide bonds.
[0072] (2) Construction of time-series fluorescent anti-counterfeiting coating Acetone dispersion powder of G-CDs@COOH-SP with a concentration of 35 mg / mL was thoroughly mixed and stirred evenly with acetone solution of hydroxy acrylic resin to obtain a uniform and stable composite spray liquid. The above spray liquid was uniformly sprayed onto the substrate surface, and after drying and curing, a time-series fluorescent anti-counterfeiting coating, G-CDs@COOH-SPcoating, was formed on the substrate surface.
[0073] (3) Construction of composite coating On the surface of the prepared time-series fluorescent anti-counterfeiting coating, an acetone solution of 0.30 g / mL polyurethane prepolymer and an acetone dispersion of 1.00 g / mL amphiphilic hollow mesoporous silica Janus microcapsules were sequentially sprayed to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer. After stepwise drying, silicone oil with a concentration of 2.50 g / mL was injected into the microcapsule pore structure to finally construct a functional composite coating, G-CDs@COOH-SP SLIPS, which has both dynamic time-series fluorescent anti-counterfeiting and excellent anti-fouling properties.
[0074] Example 6 (1) Preparation of covalently linked amide-bonded composite fluorescent products (G-CDs@COOH-SP) A certain amount of 1-butyl-3-methylimidazolium chloride, citric acid, and o-phenylenediamine (300% of the mass of citric acid) were placed in a three-necked flask. The mass of 1-butyl-3-methylimidazolium chloride was 300% of the mass of citric acid. The mixture was heated to 150 °C and reacted at this temperature for 4 h. After the reaction was completed, the resulting product was placed in a dialysis bag with a molecular weight cutoff of 800-1000 Da and dialyzed for 48 h. Finally, the product was freeze-dried to obtain green carbon dots, G-CDs.
[0075] 2,3,3-Trimethylindole and 120% (by weight) 3-bromopropionic acid of 2,3,3-trimethylindole were dissolved in toluene solution and refluxed at 120 °C for 14 h. After the reflux reaction, the product was washed with toluene and dried to obtain a reaction intermediate. Subsequently, the obtained intermediate was dissolved in ethanol solution with 100% (by weight) 5-nitrosalicylic acid of the intermediate and refluxed at 80 °C for 8 h. After the reaction was completed, the product was dried to finally obtain the carboxyl-functionalized spiropyran product, COOH-SP.
[0076] A 1 mg / mL aqueous solution of G-CDs was added to a 500% COOH-SP solution containing the G-CDs aqueous solution. A coupling agent, a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, was then added to the mixture. The mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dots was 1:1, and the mass ratio of N-hydroxysuccinimide to green carbon dots was 3:1. The mixture was reacted at room temperature for 12 h. After the reaction, the resulting product was dialyzed for 36 h in a dialysis bag with a molecular weight cutoff of 1000-1300 Da to remove residual impurities and unreacted materials. Finally, the purified product was freeze-dried to obtain a covalently linked composite fluorescent product, G-CDs@COOH-SP, via amide bonds.
[0077] (2) Construction of time-series fluorescent anti-counterfeiting coating Acetone dispersion powder of G-CDs@COOH-SP with a concentration of 50 mg / mL was thoroughly mixed and stirred evenly with acetone solution of hydroxy acrylic resin to obtain a uniform and stable composite spray liquid. The above spray liquid was uniformly sprayed onto the substrate surface, and after drying and curing, a time-series fluorescent anti-counterfeiting coating, G-CDs@COOH-SPcoating, was formed on the substrate surface.
[0078] (3) Construction of composite coating On the surface of the prepared time-series fluorescent anti-counterfeiting coating, an acetone solution of 0.40 g / mL polyurethane prepolymer and an acetone dispersion of 2.00 g / mL amphiphilic hollow mesoporous silica Janus microcapsules were sequentially sprayed to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer. After stepwise drying, silicone oil with a concentration of 2.50 g / mL was injected into the microcapsule pore structure to finally construct a functional composite coating, G-CDs@COOH-SP SLIPS, which has both dynamic time-series fluorescent anti-counterfeiting and excellent anti-fouling properties.
[0079] Figure 1 The Fourier transform infrared spectra of G-CDs, COOH-SP, and G-CDs@COOH-SP in Example 1 of this invention are shown. For COOH-SP, the Fourier transform infrared spectra are at 1720 cm⁻¹. -1 The characteristic absorption peak at 3400 cm⁻¹ is attributed to the C=O stretching vibration of the carboxyl group, while G-CDs show a peak at 3400 cm⁻¹. -1 A broad absorption band for the amino NH stretching vibration exists nearby, at 1644 cm⁻¹. -1 1398 cm -1 These correspond to the bending vibration of the amino group and the stretching vibration of the CN bond, respectively. The two are linked by an amide bond to form the G-CDs@COOH-SP complex, with COOH-SP located at 1720 cm⁻¹. -1 The characteristic peak of the carboxyl group was significantly weakened, and at 1600 cm⁻¹... -1 1518 cm -1 The characteristic absorption peaks of the amide bond appear at 1359 cm⁻¹, corresponding to the amide I band (C=O stretching vibration) and the amide II band (NH bending coupled to CN stretching vibration), respectively. -1 Attributable to the CN stretching vibration of the amide structure, 3434 cm⁻¹ -1 The broad peaks represent the superimposed stretching vibrations of residual NH and OH groups. This demonstrates that the amino groups on the surface of G-CDs undergo a dehydration condensation reaction with the terminal carboxyl groups of COOH-SP molecules, successfully forming an amide bond covalently linked structure, thus achieving stable grafting modification of spiropyran molecules on the carbon dot surface.
[0080] Figure 2 The image shows the fluorescence spectrum of G-CDs in Example 1 of this invention. The excitation peak of the G-CDs is at 420 nm and the emission peak is at 530 nm, exhibiting typical green fluorescence emission characteristics. The attached figure on the upper right side visually confirms that the carbon dot solution can emit bright green fluorescence after being irradiated by light, proving that the prepared G-CDs have excellent green fluorescence luminescence performance.
[0081] Figure 3The image shows the fluorescence spectrum of COOH-SP in Example 1 of this invention. The excitation peak of COOH-SP is at 550 nm, and the emission peak is at 650 nm, exhibiting typical red fluorescence emission characteristics. The attached image on the upper right side visually confirms that the COOH-SP solution can emit bright red fluorescence after being irradiated with light, proving that the prepared COOH-SP has excellent red fluorescence luminescence performance.
[0082] Figure 4 The fluorescence performance characterization results of the G-CDs@COOH-SP(1:2) composite material prepared in Example 1 are shown, including actual images of fluorescence colors under different 365 nm ultraviolet light illumination durations, fluorescence emission spectra corresponding to the 365 nm excitation wavelength (a), and fluorescence color CIE coordinate variation graphs (b), which can intuitively reflect the time-series fluorescence evolution of the material. Figure 4 (a) Fluorescence emission spectroscopy results show that under continuous irradiation with 365 nm ultraviolet light, the fluorescence emission intensity of the composite material exhibits a regular dynamic change with irradiation time. Specifically, the intensity of the 530 nm green fluorescence characteristic emission peak belonging to G-CDs gradually decreases with prolonged irradiation, while the intensity of the 650 nm red fluorescence characteristic emission peak belonging to COOH-SP continuously and slowly increases. This bidirectional change in fluorescence intensity, characterized by a decrease and increase, allows the overall fluorescence color of the composite material to undergo a dynamically tunable evolution from green fluorescence to yellow fluorescence to red fluorescence with irradiation time, endowing the material with unique time-sequential fluorescent anti-counterfeiting properties. Figure 4 (b) The CIE coordinate plot further verifies the time-series fluorescence change characteristics. The fluorescence color coordinates corresponding to different illumination durations show a regular shift, accurately corresponding to the fluorescence color differences at each stage. In summary, this G-CDs@COOH-SP(1:2) composite material can undergo controllable fluorescence spectrum and color changes with ultraviolet irradiation time, possessing stable and identifiable time-series fluorescence response characteristics, thus giving it time-series fluorescence anti-counterfeiting properties.
[0083] Figure 5 The figure shows the fatigue resistance test results of G-CDs@COOH-SP (1:2) prepared in Example 1 of this invention. After 35 consecutive UV irradiation cycles, G-CDs@COOH-SP (1:2) maintained stable fluorescence response characteristics even after multiple cycles of light stimulation. The dynamic change pattern of its green-red fluorescence did not show significant attenuation or disorder, and the fluorescence emission intensity did not decrease significantly. No adverse phenomena such as fluorescence quenching or response failure occurred. These results indicate that the time-series fluorescence structure constructed by G-CDs@COOH-SP exhibits excellent system stability, can withstand multiple light irradiation cycles, and possesses good fatigue resistance.
[0084] Figure 6The optical appearance of G-CDs@COOH-SP coating and G-CDs@COOH-SP SLIPS prepared in Example 1 of this invention under natural light (a) and 365 nm ultraviolet light irradiation for 60 s (b). Figure 6 The images show a comparison of the optical appearance of the G-CDs@COOH-SP coating and G-CDs@COOH-SP SLIPS prepared in Example 1 of this invention under natural light (a) and after irradiation with 365 nm ultraviolet light for 60 s (b). Figure 6 As can be seen, the two coatings show no significant difference in appearance under natural light, with essentially the same color and shape; however, after 60 seconds of irradiation with 365 nm ultraviolet light, as... Figure 6 As shown in b, the red fluorescence intensity of G-CDs@COOH-SP SLIPS is significantly higher than that of G-CDs@COOH-SP coating, indicating that the introduction of the super-slippery surface can effectively enhance the fluorescence emission intensity of the coating, further confirming the physical barrier effect of the super-slippery layer on the fluorescence quenching medium.
[0085] Figure 7 The figures show the acid and alkali resistance fluorescence stability test results of the G-CDs@COOH-SP coating and G-CDs@COOH-SP SLIPS materials prepared in Example 1 of this invention, after being immersed in solutions at pH=1, 7, and 13 for 3 days, and after irradiation with 365 nm ultraviolet light for 0 s (a) at 530 nm and 60 s (b) at 650 nm. The two groups of samples were immersed in solutions at pH=1, 7, and 13 for 3 days, respectively, and then the fluorescence intensity changes of the two groups of materials were tested and compared under the initial state of 0 s irradiation with 365 nm ultraviolet light to explore the protective effect of the SLIPS superlubricating structure on the fluorescence performance of the composite material. The G-CDs@COOH-SP SLIPS composite coating exhibits excellent acid and alkali resistance. After immersion in solutions of different pH values for 3 days, the fluorescence intensity decay rates of this composite coating were only 27.74%, 26.74%, and 35.71% at pH=1, pH=7, and pH=13, respectively. In contrast, the pure G-CDs@COOH-SP coating without the super-lubricated surface showed a significantly greater fluorescence decay after the same immersion treatment, with corresponding fluorescence intensity decay rates as high as 52.83%, 51.10%, and 56.84%, respectively. The comparative data fully demonstrates that the introduction of the SLIPS super-lubricated structure can effectively isolate the internal fluorescent functional components from the erosion and damage of acid and alkali corrosive media, significantly reduce the loss of material fluorescence performance in extreme acid and alkali environments, greatly improve the fluorescence stability of the composite material in complex acid and alkali environments, effectively ensure the stability of the material's fluorescence performance, and significantly broaden the practical application scenarios and environmental adaptability of this time-series fluorescent anti-counterfeiting material.
[0086] Figure 8 The changes in water contact angle and contact angle hysteresis of the G-CDs@COOH-SP SLIPS prepared in Example 1 of this invention after immersion in solutions with pH=1, 7, and 13 for 3 days were shown. Even after prolonged immersion in acidic and alkaline solutions of different pH values, the G-CDs@COOH-SPSLIPS maintained stable low sliding resistance characteristics. The water contact angle and contact angle hysteresis values of the samples did not show significant fluctuations or deterioration, and the overall wetting parameters showed relatively small fluctuations. Specifically, the initial water contact angle of the sample was 108.5°. After immersion in solutions with pH=1, 7, and 13 for 3 days, the contact angle slowly changed to 98.9°, 100.5°, and 93.4°, respectively, with the corresponding contact angle hysteresis slowly increasing from the initial 1.34° to 3.12°, 2.13°, and 5.88°, respectively. It can be seen that all wetting parameters remained within a stable range without significant attenuation, exhibiting significant resistance to acid and alkali corrosion. It is not easily damaged in strong acid, strong alkali, and conventional neutral environments and can maintain an intact surface protective structure for a long time.
[0087] The composite coating of this invention exhibits a continuous dynamic time-series luminescence change from green fluorescence to yellow fluorescence to red fluorescence under ultraviolet light excitation, possessing both unique dynamic anti-counterfeiting characteristics and excellent super-slippery properties with an initial water contact angle hysteresis of less than 2°. To verify its environmental resistance, this coating and a pure anti-counterfeiting coating without a super-slippery surface were immersed in solutions at pH=1, pH=7, and pH=13 for 3 days, respectively. The results showed that the fluorescence intensity decay rate of this invention was only 27.74%, 26.74%, and 35.71%, far lower than the 52.83%, 51.10%, and 56.84% of the control group. Moreover, after acid and alkali immersion, its water contact angle hysteresis could still be stably maintained at a low level of less than 6°, demonstrating excellent resistance to acid and alkali corrosion and anti-fouling durability. Furthermore, thanks to the effective physical barrier of the super-smooth surface against fluorescence quenching media such as water molecules and oxygen, the fluorescence intensity of this coating at 530 nm during initial ultraviolet irradiation is 10.27% higher than that of the pure anti-counterfeiting coating, and the fluorescence intensity at 650 nm after 60 s of irradiation is 35.18% higher, achieving a synergistic enhancement of anti-counterfeiting luminescent signal intensity and long-term stability.
[0088] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A composite coating based on carbon dots, spiropyran, and a super-lubricating surface, characterized in that, The system includes a substrate, on the surface of which a time-series fluorescent anti-counterfeiting coating is disposed, and the surface of the time-series fluorescent anti-counterfeiting coating is disposed with an ultra-slippery surface layer; the time-series fluorescent anti-counterfeiting coating contains a composite fluorescent product, which includes green carbon dots and carboxyl-functionalized spiropyran, and the green carbon dots and carboxyl-functionalized spiropyran are covalently linked by amide bonds; the composite coating exhibits continuous dynamic time-series luminescence changes of green fluorescence, yellow fluorescence and red fluorescence under ultraviolet light excitation.
2. The composite coating based on carbon dots, spiropyran, and a super-lubricating surface according to claim 1, characterized in that, The super-slippery surface layer comprises a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer, wherein the Janus microcapsule pore structure of the amphiphilic hollow mesoporous silica Janus microcapsule layer is filled with silicone oil.
3. The composite coating based on carbon dots, spiropyran, and a super-lubricating surface according to claim 1, characterized in that, The initial water contact angle hysteresis of the composite coating is less than 2°.
4. A method for preparing a composite coating based on carbon dots, spiropyran, and a super-lubricating surface as described in any one of claims 1-3, characterized in that, Includes the following steps: 1) Mix ionic liquid, carbon source and nitrogen source, heat to 80-150℃ and react at a constant temperature for 2-4 hours, then perform a first dialysis and freeze-drying to obtain green carbon dots; the mass ratio of ionic liquid to carbon source is 3:1, and the mass ratio of nitrogen source to carbon source is (1-3):
1. 2) 2,3,3-trimethylindole and 3-bromopropionic acid are dissolved in a first organic solvent and subjected to a first reflux reaction to obtain an intermediate product; the intermediate product is then dissolved in a second organic solvent and subjected to a second reflux reaction to obtain a carboxyl-functionalized spiropyran; the mass ratio of 3-bromopropionic acid to 2,3,3-trimethylindole is (0.8-1.2):1; the mass ratio of 5-nitrosalicylic acid to the intermediate product is (0.6-1.0):1; 3) Mix the green carbon dot aqueous solution with the carboxyl-functionalized spiropyran solution, add a coupling agent, react at room temperature for 6-12 h, and then perform a second dialysis and freeze-drying to obtain a composite fluorescent product covalently linked by amide bonds; 4) The composite fluorescent product powder is added to the organic solution of hydroxyl acrylic resin to prepare a composite spraying liquid, which is then sprayed onto the substrate surface, dried and cured to obtain a time-series fluorescent anti-counterfeiting coating. 5) An ultra-slippery surface layer is prepared on the surface of the time-series fluorescent anti-counterfeiting coating to obtain the composite coating.
5. The preparation method according to claim 4, characterized in that, The ionic liquid in step 1) is 1-butyl-3-methylimidazolium chloride, the carbon source is citric acid, and the nitrogen source is o-phenylenediamine; the conditions for the first dialysis treatment include: a molecular weight cutoff of 800-1000 Da and a time of 12-48 h.
6. The preparation method according to claim 4, characterized in that, In step 2), the first organic solvent is toluene, the temperature of the first reflux reaction is 120-140 °C, and the time is 10-14 h. After the first reflux reaction is completed, the product is washed and dried with toluene to obtain the reaction intermediate. The second organic solvent is an ethanol solution, the temperature of the second reflux reaction is 60-80 °C, and the time is 6-8 h. After the second reflux reaction is completed, the product is dried to obtain the carboxyl-functionalized spiropyran product.
7. The preparation method according to claim 4, characterized in that, In step 3), the concentration of the green carbon dot aqueous solution is 1 mg / mL, and the volume ratio of the carboxyl-functionalized spiropyran solution to the green carbon dot aqueous solution is (1-5):1; the coupling agent is a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, the mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to green carbon dot is (1-5):1, and the mass ratio of N-hydroxysuccinimide to green carbon dot is (1-3):1; the conditions for the second dialysis treatment include: a molecular weight cutoff of 1000-1300 Da and a time of 12-48 h.
8. The preparation method according to claim 4, characterized in that, In step 4), the organic solution of the hydroxy acrylic resin is an acetone solution of the hydroxy acrylic resin; the concentration of the composite spraying liquid is 10 mg / mL - 50 mg / mL.
9. The preparation method according to claim 4, characterized in that, In step 5), the step of preparing the super-slippery surface layer includes: sequentially spraying an acetone solution of polyurethane prepolymer and an acetone dispersion of amphiphilic hollow mesoporous silica Janus microcapsules onto the surface of the time-series fluorescent anti-counterfeiting coating to form a polyurethane prepolymer layer and an amphiphilic hollow mesoporous silica Janus microcapsule layer, drying in steps, and injecting silicone oil into the Janus microcapsule pore structure of the acetone dispersion of amphiphilic hollow mesoporous silica Janus microcapsules to obtain the composite coating; The acetone solution concentration of the polyurethane prepolymer was 0.10 g / mL - 0.40 g / mL, the acetone dispersion concentration of the amphiphilic hollow mesoporous silica Janus microcapsules was 1.0 g / mL - 2.0 g / mL, and the concentration of the silicone oil was 0.50 g / mL - 2.50 g / mL.
10. The application of the composite coating according to any one of claims 1-3 in high-end document recognition, anti-counterfeiting of food and drug packaging, and anti-counterfeiting of precision device marking.
Citation Information
Patent Citations
A metal-organic framework-loaded spiropyran photoinduced dual-color material and preparation method thereof
CN116554868B